2021
DOI: 10.3389/fcell.2021.629681
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Methicillin-Resistant Staphylococcus Aureus From Methicillin-Sensitive Staphylococcus Aureus and Molecular Characterization in Quanzhou, China

Abstract: To distinguish Methicillin-Resistant Staphylococcus aureus (MRSA) from Methicillin-Sensitive Staphylococcus aureus (MSSA) in the protein sequences level, test the susceptibility to antibiotic of all Staphylococcus aureus isolates from Quanzhou hospitals, define the virulence factor and molecular characteristics of the MRSA isolates. MRSA and MSSA Pfam protein sequences were used to extract feature vectors of 188D, n-gram and 400D. Weka software was applied to classify the two Staphylococcus aureus and performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 100 publications
1
11
0
1
Order By: Relevance
“… Tsouklidis et al (2020) ) reported that a PVL-positive toxin was detected in more than 97% of CA-MRSA strains, but this toxin was not detected in HA-MRSA strains. In contrast, Bai et al (2021) ) found no significant difference between CA-MRSA (51.2%) and HA-MRSA (40.9%) strains in terms of the presence of PVL-positive toxin. In the present study, the positivity rates for the gene encoding PVL among the CA- and HA-MRSA isolates were 53.1 and 35.7%, respectively; therefore, the abovementioned results showing no significant difference were verified by performing further experiments ( p = 0.142; Table 5 ).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“… Tsouklidis et al (2020) ) reported that a PVL-positive toxin was detected in more than 97% of CA-MRSA strains, but this toxin was not detected in HA-MRSA strains. In contrast, Bai et al (2021) ) found no significant difference between CA-MRSA (51.2%) and HA-MRSA (40.9%) strains in terms of the presence of PVL-positive toxin. In the present study, the positivity rates for the gene encoding PVL among the CA- and HA-MRSA isolates were 53.1 and 35.7%, respectively; therefore, the abovementioned results showing no significant difference were verified by performing further experiments ( p = 0.142; Table 5 ).…”
Section: Discussionmentioning
confidence: 81%
“…However, different regions have reported variations in the percentages of PVL-positive isolates. The detection rates of PVL were 11.1% in Taiwan, 45.2% in Guangzhou, 47.6% in Hainan, and 47.7% in Quanzhou (Wang et al, 2010;Xie et al, 2016;Li et al, 2019;Bai et al, 2021). Furthermore, a nationwide survey of MRSA isolates obtained from Chinese children at eight hospitals revealed that 40% of the isolates were PVL-positive (Geng et al, 2010b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methicillin-resistant Staphylococcus aureus (MRSA) and even vancomycin-resistant S. aureus (VRSA) have already threatened human health. MRSA has gained over 60% of all isolated S. aureus , and the incidence of MRAS has risen to 49% in the United States ( 3 ). Novel pathogen-specific therapeutic strategies for the prevention or treatment of serious bacterial infections have emerged, such as monoclonal antibodies (MAbs), nanomaterials, phages, and anti-virulence treatments ( 4 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…HA-CoPS isolates, the overall susceptibility to the various antibiotics tested was: cefoxitin (31%), vancomycin (55.2%), clindamycin (100%), sulfamethoxazole/trimethoprim (100%), rifampin (100%), and quinupristin (100%), respectively. Bai et al [40] and Shariati et al [41] studies showed similar results. Accordingly, clindamycin, sulfamethoxazole/trimethoprim, rifampin, and quinupristin seem to be more effective against HA-CoPS.…”
Section: Antibiotic Susceptibility Testmentioning
confidence: 55%